Effect of Cytoplasmic Tail Truncations on the Activity of the M(2) Ion Channel of Influenza A Virus - Tobler, Kurt (American Society for Microbiology, 1999)
The M(2) protein of influenza A virus forms a proton channel that is required for viral replication. The M(2) ion channel is a homotetramer and has a 24-residue N-terminal extracellular domain, a 19-residue transmembrane domain, and a 54-residue cytoplasmic tail. We show here that the N-terminal methionine residue is cleaved from the mature protein. Translational stop codons were introduced into the M(2) cDNA at residues 46, 52, 62, 72, 77, 82, 87, and 92. The deletion mutants were designated truncx, according to the amino acid position that was changed to a stop codon. We studied the role of the cytoplasmic tail by measuring the ion channel activity (the current sensitive to the M(2)-specific inhibitor amantadine) of the cytoplasmic tail truncation mutants expressed in oocytes of Xenopus laevis. When their conductance was measured over time, mutants trunc72, trunc77, and trunc92 behaved comparably to wild-type M(2) protein (a decrease of only 4% over 30 min). In contrast, conductance decreased by 28% for trunc82, 27% for trunc62, and 81% for trunc52 channels. Complete closure of the channel could be observed in some cells for trunc62 and trunc52 within 30 min. These data suggest that a role of the cytoplasmic tail region of the M(2) ion channel is to stabilize the pore against premature closure while the ectodomain is exposed to low pH.